An investigation on bond between FRP stay-in-place formwork and concrete - Goyal, R.; Mukherjee, Abhijit; Goyal, S. (Elsevier BV, 2016)
FRP stay-in-place (SIP) formworks are designed to act as a support for casting concrete and as a tension reinforcement when the concrete is cured. For composite action between the formwork and concrete, proper bond between them is essential. This investigation focuses on the role of adhesives for the bond development. Two different bond mechanisms, aggregate bonding and adhesive bond, are investigated using three different adhesives. A novel experimental set up is prepared to evaluate the bond. The load capacities and failure modes were examined. Load-deflection, load-slip and load-strain curves have been plotted to evaluate the bond mechanisms. A finite element model is developed that is able to accurately predict the ultimate pullout load and load-slip relationships. The results show that the types of resins have a great impact on the bond. It is recommended to use the wet-bond technique with special adhesives.